Sistem dan Prosedur Operasional Pelayanan Kapal dan Barang pada PT. Pelayaran Berkat Usaha Mandiri Panjang Lampung - Maria Seprida Purba; Dirhamsyah Dirhamsyah; Yuna Sutria (Jurnal Transformasi Bisnis Digital, 2025)
This paper aims to determine the system and procedures for ship and goods service activities at PT. Pelayaran Berkat Usaha Mandiri Panjang Lampung at Panjang Port, Bandar Lampung. The management of the ship is managed by agencies in the port environment. Not only that, operational agents are also required to understand the workflow of the Inaportnet application so that ship operational activities are completed on time. The author uses several methods such as; observation method, interview method, documentation method, and the existence of research files. Based on the results of the observations, the author can conclude that the System and Procedures for Ship and Goods Service Operations at PT. Pelayaran Berkat Usaha Mandiri acts as an agent who is responsible for serving agency ships since the ship will arrive, namely including the clearance in process using the Inaportnet system application, in addition, the agent also takes ship documents and continues with the clearance out process until the ship will leave the port to go to the next port. In order to facilitate operational activities, supporting documents are needed for the clearance in and clearance out processes of the ship.